IL-4 and IL-17 Are Required for House Dust Mite-Driven Airway Hyperresponsiveness in Autoimmune Diabetes-Prone Non-Obese Diabetic Mice - Foray, Anne-Perrine; Dietrich, Céline; Pecquet, Coralie; Machavoine, François; Chatenoud, Lucienne; Leite-de-Moraes, Maria (Frontiers in Immunology, 2021)
Allergic asthma is characterized by airway inflammation with a Th2-type cytokine profile, hyper-IgE production, mucus hypersecretion and airway hyperreactivity (AHR). It is increasingly recognized that asthma is a heterogeneous disease implicating complex immune mechanisms resulting in distinct endotypes observed in patients. In this study, we showed that Non Obese Diabetic (NOD) mice, which spontaneously develop autoimmune diabetes, undergo more severe allergic asthma airway inflammation and AHR than pro-Th2 BALB/c mice upon house dust mite (HDM) sensitization and challenge. The use of IL-4-deficient NOD mice and the in vivo neutralization of IL-17 demonstrated that both IL-4 and IL-17 are responsible by the exacerbated airway inflammation and AHR observed in NOD mice. Overall, our findings indicate that autoimmune diabetes-prone NOD mice might become useful as a new HDM-induced asthma model to elucidate allergic dysimmune mechanisms involving Th2 and Th17 responses that could better mimic some asthmatic endoytpes.